2020
DOI: 10.3389/fimmu.2020.00369
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Immune Landscapes, Genetic Subtypes and Responses to Immunotherapy in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is highly heterogeneous at the genetic and molecular level, which has major repercussions on the efficacy of immunotherapy. A small subset of CRCs exhibit microsatellite instability (MSI), a molecular indicator of defective DNA mismatch repair (MMR), but the majority are microsatellite-stable (MSS). The high tumor mutational burden (TMB) and neoantigen load in MSI tumors favors the infiltration of immune effector cells, and antitumor immune responses within these tumors are strong relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
317
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(338 citation statements)
references
References 193 publications
(247 reference statements)
19
317
1
1
Order By: Relevance
“…Immune-associated genes are well known to be overexpressed in dMMR CRC but few studies have investigated the functional significance of these genes for the antitumor immune response. 1,3 Furthermore, most reports are based on whole tissue transcript analysis, making it difficult to determine the relative contribution of the CRC cells themselves to the expression of immune genes in the tissue. 23 In seeking to better understand the factors governing TIL recruitment into dMMR CRCs, we examined expression of various chemokines in data obtained from The Cancer Genome Atlas PanCancer Atlas data set.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune-associated genes are well known to be overexpressed in dMMR CRC but few studies have investigated the functional significance of these genes for the antitumor immune response. 1,3 Furthermore, most reports are based on whole tissue transcript analysis, making it difficult to determine the relative contribution of the CRC cells themselves to the expression of immune genes in the tissue. 23 In seeking to better understand the factors governing TIL recruitment into dMMR CRCs, we examined expression of various chemokines in data obtained from The Cancer Genome Atlas PanCancer Atlas data set.…”
Section: Resultsmentioning
confidence: 99%
“…Colorectal cancer (CRC) is a prevalent and often fatal disease initiated by either loss of the tumor suppressor APC or the DNA mismatch repair gene MLH1. 1,2 Whereas APC inactivation promotes large scale DNA damage leading to chromosomal instability (CIN), MLH1 inactivation promotes hypermutability in the form of genome-wide point mutations due to deficient mismatch repair (dMMR). Although accounting for only 15-20% of CRCs, dMMR CRCs are of particular interest due to their potent immune-stimulating capacity and overall favorable patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these, TMB is becoming a hot biomarker for various cancers [29][30][31][32][33][34][35][36] . However, the role of TMB in colon cancer is still unde ned 14,34,36,37 . In this study, we rstly and comprehensively explored the role of tumor mutation burden in clinical signi cance, immunotherapy response predictor, and immune cell in ltration in colon cancer using TCGA database.…”
Section: Discussionmentioning
confidence: 99%
“…MSI in cancers is characterized by a tumor mutation burden (TMB), de ned as the number of DNA damages, including somatic single variant (SNV), insertions, deletions and frameshift mutations 12,13 . Previous studies demonstrated TMB was strong relative to immune checkpoint inhibitors (ICI) and immune cell in ltration in various cancers [14][15][16][17][18] , which are heavily associated with response to immunotherapy and tumor behavior [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, alterations in DNA repair genes such as the MMR genes, POLE and HR genes have been shown to have a positive predictive effect and are correlated to increased TMB values (83)(84)(85)(86). In contrast, other gene alterations such as JAK1/2 and STK11/LKB1, KEAP1 and PTEN mutations are related to resistance to PD-1 Blockade (80,(87)(88)(89).…”
Section: Immunotherapy Biomarkersmentioning
confidence: 99%